An Enrichment of CRISPR and Other Defense-Related Features in Marine Sponge-Associated Microbial Metagenomes - Horn, Hannes; Slaby, Beate M.; Jahn, Martin T.; Bayer, Kristina; Moitinho-Silva, Lucas; Förster, Frank; Abdelmohsen, Usama R.; Hentschel, Ute (Frontiers in Microbiology, 2016)
Many marine sponges are populated by dense and taxonomically diverse microbial consortia. We employed a metagenomics approach to unravel the differences in the functional gene repertoire among three Mediterranean sponge species, Petrosia ficiformis, Sarcotragus foetidus, Aplysina aerophoba and seawater. Different signatures were observed between sponge and seawater metagenomes with regard to microbial community composition, GC content, and estimated bacterial genome size. Our analysis showed further a pronounced repertoire for defense systems in sponge metagenomes. Specifically, Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR), restriction modification, DNA phosphorothioation and phage growth limitation systems were enriched in sponge metagenomes. These data suggest that defense is an important functional trait for an existence within sponges that requires mechanisms to defend against foreign DNA from microorganisms and viruses. This study contributes to an understanding of the evolutionary arms race between viruses/phages and bacterial genomes and it sheds light on the bacterial defenses that have evolved in the context of the sponge holobiont.